L’hyperactivité/TDAH : un analyseur de l’apport des neurosciences aux pratiques médiatiques, éducatives et à la formation des travailleurs sociaux - Sébastien PONNOU (Éducation et Socialisation)
We studied the representations of ADHD in French television programs (N = 60), newspaper articles (N = 159) and websites (N = 50) between 1990 and 2015. We also analyzed the articles devoted to ADHD in the specialized literature for social workers (N = 93) and questioned social work students about their representations of this pathology (N = 99). We focused our analysis on the neurologic and genetic risk factors for ADHD, and on the effects of drugs on school achievement. The cross-analysis of ADHD representations shows recurrent distortions of neuroscience data. The study highlights conflicts of interest that may contribute to these distortions. Deviations from international consensuses skyrocket during our study period. This misinformation hides social and environmental risk factors that may be subject to appropriate socio-educational policies and practices.